Biodiesel production from waste cooking oil in an oscillatory flow reactor. Performance as a fuel on a TDI diesel engine - García-Martín, Juan Francisco; Barrios, Carmen C.; Alés-Álvarez, Francisco-Javier; Dominguez-Sáez, Aida; Alvarez-Mateos, Paloma (Renewable energy, 2018)
This paper describes the biodiesel production from waste cooking oil (50% (v/v) olive oil/sunflower oil) in an oscillatory flow reactor (OFR) in batch mode. We mainly focused on the characteristics of the biodiesel and its performance as a fuel. First at all, we verified that biodiesel yield in OFR was higher than in stirred tank reactor (STR) under the same experimental conditions, and that composition and properties of the resulting biofuel did not depend on reactor type. Besides, biodiesel production in OFR took half the time than in STR. Subsequently, we modify some OFR operational parameters to assess their influence on biodiesel yield. The most suitable conditions were found to be 6:1 methanol to waste cooking oil molar ratio, 0.67 Hz oscillation frequency and 30 min reaction time. Finally, the biofuel obtained was tested in a 2.0 TDI 140 hp EURO4 engine installed on an engine test bench. Specific fuel consumption, particle size distribution and concentration of exhaust gas sample pollutants and were analysed running with commercial diesel, 50% (v/v) diesel/biodiesel blend (B50) and biodiesel (B100) in order to ensure the viability of using this biofuel in vehicle engines. •Oscillatory flow reactor achieved higher biodiesel yields.•Biodiesel composition and properties did not depend on reactor type.•Biodiesel increased fuel consumption and NOx emissions.•Biodiesel decreased particle size and total emissions.•B50 showed better engine performance than B100.